An estradiol releasing, proangiogenic hydrogel as a candidate material for use in soft tissue interposition. Issue 5 (25th March 2019) - Mangır, Naşide; Eke, Gozde; Hasirci, Nesrin; Chapple, Christopher R.; Hasirci, Vasif; MacNeil, Sheila
Abstract: Introduction and Objectives: Soft tissue interposition (STI) using local and/or regional flaps is often necessary in urogenital reconstruction to stimulate wound healing and prevent recurrence. Harvesting STI flaps can cause donor site morbidity and may not be available in some patients. In this study, we designed estradiol (E2) releasing hydrogel that could be used as an alternative to a STI flap and to investigate its ability to stimulate tissue production and angiogenesis. Materials and Methods: A hydrogel was constructed by crosslinking a solution of estradiol, methacrylated gelatin (15%, w/v), and methacrylated hyaluronic acid (1%, w/v). The release of estradiol was measured using a UV‐spectrophotometer (λmax  = 220 nm). Angiogenesis was evaluated by an ex ovo chicken embryo chorioallantoic membrane (CAM) assay. Results: Estradiol was gradually released from the hydrogel over 21 days. The hydrogels could be easily manipulated with surgical forceps without any deformation. The hydrogels significantly increased collagen production of human dermal fibroblasts (HDFs). Scanning electron microscopic examination demonstrated that HDFs produced significantly more extracellular matrix (ECM) on estradiol releasing hydrogels compared with the controls. Estradiol releasing hydrogels doubled the number of blood vessels growing toward the hydrogel compared with the controls (vasculogenic index, 59.6 [±6.4] and 25.6 [±4.0], respectively; [ P  < 0.05]). Conclusion: We present a proangiogenic, degradable hydrogel that can be used as an off‐the‐shelf available substitute to traditional STI flaps. This is achieved by using estradiol as a potent stimulator of new tissue production and new blood vessel formation.